(untitled) (Italian Journal of Public Health, 2006)
Dear Sirs, The forth phase of the epidemiological and demographic transition has brought populations to a lower fertility status with extended life expectancy.The diseases of this phase are chronic and complex diseases, which mainly stem from the complex interaction of the human genome with life style factors. Cardiovascular and cerebrovascular diseases, cancers, diabetes and osteoporosis are among major chronic and complex diseases,which account for approximately 86% of all deaths and 77% of the burden of disease in Europe (Preventing chronic diseases: a vital investment. Geneva,World Health Organization, 2005). The way we view health and disease from the perspective of chronic and complex diseases, the main determinants of health - including those that are biological and social, is illustrated in Figure 1. The strong interaction of biological and genetic factors with life style factors in the development of chronic and complex diseases has brought us to a new understanding of ‘genetics’, where genetics is not only related to the study of rare hereditary disorders, as understood in ‘conventional’ medical genetics.As science reveals more about the genetic basis of these common diseases, genetics and genomics are increasingly becoming a part of daily practice in various branches of medicine.At this point,new issues and problems arise related to various aspects of this new potential practice; such as the implications for nutrigenetics and pharmacogenetics; the clinical utility and validity of genetic tests; as well as the ethical, legal and social aspects of public health genomics. Public Health Genomics European Network (PHGEN), an EU project that runs from January 2006 to December 2008, aims to deal with these issues in the European context.This networking exercise covers all EU Member States, Applicant Countries and EFTA-EEA (European Free Trade Association-European Economic Area) countries.